2014
DOI: 10.1007/s00216-014-8223-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of hydrazine-based derivatization reagents for improved sensitivity and detection of carbonyl containing compounds using MALDI-MSI

Abstract: This document is the author deposited version. You are advised to consult the publisher's version if you wish to cite from it. Published versionFLINDERS, Bryn, MORRELL, Josie, MARSHALL, Peter S., RANSHAW, Lisa E. and CLENCH, Malcolm (2015). The use of hydrazine-based derivatization reagents for improved sensitivity and detection of carbonyl containing compounds using MALDI-MSI. Analytical and Bioanalytical Chemistry, 407 (8), 2085-2094. Copyright and re-use policy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 16 publications
(25 reference statements)
0
41
0
Order By: Relevance
“…for analysing bacterial biofilms, 167 three-dimensional cell cultures, 168 mouse brain, 169 or rat spinal cord sections. 180 MALDI MSI has already been employed as a tool to close the gap between metabolome changes in response to drug administration and certainly will be continued in the future in clinical settings. Within the reported lipidomic MALDI MSI studies, insects are the smallest animal bodies investigated, ranking from complete insect bodies, such as drosophila melanogaster flies to paderus riparius beetles.…”
Section: Metabolomicsmentioning
confidence: 99%
“…for analysing bacterial biofilms, 167 three-dimensional cell cultures, 168 mouse brain, 169 or rat spinal cord sections. 180 MALDI MSI has already been employed as a tool to close the gap between metabolome changes in response to drug administration and certainly will be continued in the future in clinical settings. Within the reported lipidomic MALDI MSI studies, insects are the smallest animal bodies investigated, ranking from complete insect bodies, such as drosophila melanogaster flies to paderus riparius beetles.…”
Section: Metabolomicsmentioning
confidence: 99%
“…In a study from Richard Caprioli's lab (Vanderbilt university), Chacon et al first showed that it is possible to derivatize a drug analyte directly from the tissue surface [116]. In a second preliminary study, Flynders and colleagues used a tailor made hydrazinebased derivative, 4-dimethylamino-6-(4-methoxy-1-naphthyl)-1,3,5-triazine-2-hydrazine (DMnTH), to react with steroids to form hydrazones directly on the tissue surface, which improved their mass spectral ionization efficiency and detection [117]. Since DMnTH served as the MALDI matrix, no special steps were required to derivatize the compounds in tissue.…”
Section: Derivatizationmentioning
confidence: 99%
“…Such an in-situ derivatization approach was further developed to target different chemical functionalities. Hydrazine-base matrices were used to specifically react with carbonyl groups, improving desorption/ionization of corticoids [2,3] and of carbonyl-containing phospholipids [4], or enabling MALDI mass analysis of small gaseous carbonyl compounds [5,6]. Enhancement of MALDI efficiency was reported for ␣-dicarbonyl compounds when using 9-(3,4-diaminophenyl)acridine as a reactive matrix [7], whereas 3-aminoquinoline was advantageously employed in MALDI-MS of oligosaccharides [8].…”
Section: Introductionmentioning
confidence: 98%